BUSINESS PROCESS RE-ENGINEERING: WORTHWHILE LESSONS FROM QUALITY OF WORKLIFE AND EMPLOYEE INVOLVEMENT - Marcham Darokah; Mr. Michael K. Muchiri (Faculty of Economics and Business, Universitas Gadjah Mada, 2000)
Business process reengineering is changing the way employees work, both collectively and individually. Reengineering is reunfying the tasks into coherent business processes with changes such as adding new tasks to each job, reducing functional specialization of jobs, moving decision making down to the lowest levels of the organization, installing multiple process paths, and organizing workers into teams. Reengineering means that jobs will be more fluid, more complex, and less predictable. Jobs change, roles change, job preparation changes, values change, and compensation and performance measures change (Hammer & Champy, 1993). This blurs the functional structures and concentrates on process driven organization in the hope of aiding effectiveness for breakthrough gains and dramatic performance. Yet many reengineering projects either fail or do not produce the desired results as the people issues are not addressed satisfactorily. This paper proposes a Bottom Line = Quality Of Worklife / Employee Involvement Model which argues that reengineering can learn from the Quality of Worklife and Employee Involvement paradigm in handling the emerging dissonances from the change initiative. Spea7ically, the paper assesses the Implied shift in mode of performance appraisal, the emerging roles of human resource development and the subsequent implications on training, compensation, and general employee satisfaction for the success of BPR.